Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification - Schodde, Richard; Tennyson, Alan J.d.; Groth, Jeff G.; Lai, Jonas; Scofield, Paul; Steinheimer, Frank D. (Zootaxa, 2017)
On-going conflict in use of the name Diomedea exulans Linnaeus, 1758 for different taxa of the great albatrosses (Wandering Albatross complex) is resolved by neotypification, fixing the name to the large subantarctic form formerly often known as D. chionoptera Salvin, 1896. Application of all scientific names in the complex is reviewed, an annotated synonymy for the large subantarctic form is provided, available names for smaller, temperate-zone forms are listed, and unavailable and otherwise invalid names referable to the complex are identified. Syntypes of D. chionoptera and D. spadicea J.F. Gmelin, 1789 are lectotypified as well, fixing their names as synonyms of D. exulans to prevent possible disturbance to in-use names for the smaller, temperate-zone forms.